(3fRgI GdYbhd GdRcjI aj TQM GdaUhd GdaQVjIs - (3jYbhH Hf GjhH Hf YHO GdhGMO GdehGMOjs
(3ChdgG (B:s
(3eef dg QZHI ai JYde GdaQGjV hGRjO dg Ydi GdaUhd GdCKfi YTQ GdefShHI dHYV JdGejP CHj GdYHGS s
(3BNQgG (B:s
(3abGd HdZfi Gf HdZfi Gf GeQGI LGA Hi Ydi Hf CHj WGdH QVi Gddg Yfg hbO hVY QLdg ai QcGH QMdI QShd Gddg Udi Gddg Ydjg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 493) s
Keywords: (3Yde GdaQGFVs